2014
DOI: 10.1080/00221686.2014.919965
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the role of spanwise vorticity and vortex filaments in the outer region of open-channel flow

Abstract: The dynamic importance of spanwise vorticity and vortex filaments has been assessed in steady, uniform open-channel flows by means of particle image velocimetry (PIV). By expressing the net force due to Reynolds' turbulent shear stress, ( )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 57 publications
8
13
0
Order By: Relevance
“…The size of the camera viewing area is 32 × 20 mm such that the spatial resolution is 24.5 pixels/mm. Based on the flow velocity in our experiment, the interval time of 2 ms assured that the maximum particle displacement between two consecutive frames is 5 pixels, which satisfies the one-quarter rule for PIV correlation analysis [44]. For more specific details of the PIV setup, see the recent work of Qi et al [45].…”
Section: Methodssupporting
confidence: 53%
“…The size of the camera viewing area is 32 × 20 mm such that the spatial resolution is 24.5 pixels/mm. Based on the flow velocity in our experiment, the interval time of 2 ms assured that the maximum particle displacement between two consecutive frames is 5 pixels, which satisfies the one-quarter rule for PIV correlation analysis [44]. For more specific details of the PIV setup, see the recent work of Qi et al [45].…”
Section: Methodssupporting
confidence: 53%
“…For the present application, the final interrogation window size was 32 × 32 pixels which have an overlap of 50%, that is the adjacent velocity vector interval is 16 pixels. Based on the flow velocity in our experiment, the interval time of 2 ms assured that the maximum particle displacement between two consecutive frames is 5 pixels, which satisfies the one-quarter rule for PIV correlation analysis [32,33]. The accuracy of the velocity vectors is approximately 0.1 pixels, which corresponds to approximately 0.7% of the full-scale velocity in the present measurement.…”
Section: Experimental Setup and Methodologysupporting
confidence: 53%
“…The experimental results of Apsilidis et al [12] also showed a similar mechanism. Meanwhile, previous research [28] has shown that the population of prograde vortices in the incoming turbulent open channel flow changes with the Reynolds number. Therefore, the evolution and dynamics of the turbulent HV system are anticipated to be influenced by the Reynolds number, as indicated by previous investigations [12,17].…”
Section: Strength Variation Of Phvmentioning
confidence: 98%